2012
DOI: 10.3382/ps.2012-02182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of prebiotic mannan-oligosaccharides and probiotic mixture on growth performance of broilers subjected to chronic heat stress

Abstract: The present study was aimed at elucidating the effects of supplementing mannan-oligosaccharides (MOS) and probiotic mixture (PM) on growth performance, intestinal histology, and corticosterone concentrations in broilers kept under chronic heat stress (HS). Four hundred fifty 1-d-old chicks were divided into 5 treatment groups and fed a corn-soybean diet ad-libitum. The temperature control (CONT) group was held at the normal ambient temperature. Heat stress broilers were held at 35 ± 2°C from d 1 until the term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
196
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(235 citation statements)
references
References 32 publications
31
196
2
6
Order By: Relevance
“…Dietary pre biotics, including inulin, yeast cell wall extracts, lactulose and GOS are usually fed at concentrations up to 0.2% (weight/volume) of diet [140][141][142][143][144][145][146] .…”
Section: Conferring a Health Benefitmentioning
confidence: 99%
“…Dietary pre biotics, including inulin, yeast cell wall extracts, lactulose and GOS are usually fed at concentrations up to 0.2% (weight/volume) of diet [140][141][142][143][144][145][146] .…”
Section: Conferring a Health Benefitmentioning
confidence: 99%
“…Otherwise, the immune reaction could result in reduction of feed intake, growth disturbance and weight loss. As example, Sohail et al, (2012) recorded in broiler exposed to chronic heat stress a reduction of 16.4% of feed intake, of 32.6% of body weight and an increasing of feed conversion ratio of 25.6%.…”
Section: Sensory Analysis Of the Pectoralis Major Of Indigenous Chickenmentioning
confidence: 99%
“…Although many studies have clearly elucidated the thermoneutral zone of broilers (18)(19)(20)(21)(22) o C; Charles, 2002), it is not easy to maintain that temperature in a specific area or a period or the combination of both. Recent studies have demonstrated that heat stress has affected broiler productivity by reducing feed intake and efficiency, body weight, meat quality, and survivability (Sohail et al, 2012;Lu et al, 2007). Also, it has been shown that heat stress had immunosuppressant effects on birds and resulted in decreasing weights of lymphoid organs, total circulating antibodies, and phagocytic ability of macrophages (Quinteiro-Filho et al, 2012).…”
Section: Introductionmentioning
confidence: 99%